De-Centering the “West” in Cross-Cultural Philosophy: Philosophical Pedagogy in the Emory-Tibet Science Initiative - Peña-Guzmán, David M.; Locke, Jessica (Frontiers in Communication, 2021)
This article explores the author’s experience teaching in ETSI as an instance of a cross-cultural intellectual encounter. It develops an account of cross-cultural encounters as defined by two moments: first, a moment of cultural shock when the encounter rebounds on the self, leading one to question one’s assumptions about the world; and second, a moment of possibility where the self, after interrogating its own ways of thinking, can pivot to accommodate a detour from its past disciplinary and cultural habits. Here, the authors use the writings of the Argentinian feminist theorist María Lugones and the North American philosopher Frederick Elliston to clarify the nature of these moments.